Comparison of Pre and Postoperative Astigmatism after Cataract Extraction by Phacoemulsification through a 3.2 MM Clear Corneal Superotemporal Incision - Anwar, M. Shakaib (Pakistan Journal of Ophthalmology, 2014)
Purpose: To evaluate the difference between pre and postoperative astigmatism in patients undergoing cataract extraction by phacoemulsification with intraocular lens implantation through 3.2 mm superotemporal clear corneal incision. Material and Methods: A prospective study was performed on 144 eyes of 132 patients. They were operated upon for cataract between 12/01/2007 and 31/12/2012 by a single eye surgeon at a private set up. Follow up period was from 6 month to five years (mean 33 months). The patients included in this study, underwent cataract surgery by phacoemulsification through 3.2 mm superotemporal clear corneal incision. Their mean age at the time of surgery was 50.5 years (range: 25 to 76 years). They were divided into two groups depending upon, “With the Rule” (Group A) or “Against the Rule”(Group B), pre operative astigmatism. Results: Before surgery, mean astigmatism in group A patients was -0.83 D (Diopter) and in those of group B was -0.76 D. After the surgery, mean astigmatism in group A patients was -1.10 D and in those of group B was -1.10 D. The mean increase in astigmatism post operatively in the two groups was 0.27 D and 0.34 D respectively. Conclusion: Superotemporal clear corneal incision of 3.2 mm size is favourable in terms of wound stability and the final optical outcome. When followed up over a long time, the post operative astigmatism approaches almost the preoperative value although there may be a negligible increase in it. Key words: Astigmatism, Phacoemulsification, Intraocular lens.